Assessing the prevalence of Staphylococcus aureus in infertile male patients in Tabriz, northwest Iran - Aylin Esmailkhani; Mohammad Taghi Akhi; Javid Sadeghi; Behrooz Niknafs; Abed Zahedi Bialvaei; Laya Farzadi; Nooshafarin Safadel (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Staphylococcus aureus is an infrequent, but one of the most successful bacteria that associated with infertility and are able to spermatozoa immobilization and agglutination. Objective: The aim of present study was to determine the frequency of S. aureus in semen obtained from infertile male patients in northwest Iran. Materials and Methods: Seminal fluids of 100 infertile men were evaluated. Standard semen examination was done according to World Health Organization guidelines. After isolation and identification of S. aureus isolates according to reference methods, determination of susceptibility against important antibiotics and polymerase chain reaction were performed to identify mecA and tst genes. Results: Data obtained from the present study shows that 16% of infertile male patients were colonized by S. aureus. Ten (62.5%) of the individuals had abnormal seminal fluid sperm motility and morphology and three (18.8%) of them had an abnormal seminal fluid density, whereas after washing with albumin-saline declined to 5 (31.3%), 4 (25%) and 1 (6.3%), respectively. The antibiogram results showed that, except penicillin, other antibiotics have high activity on isolates. Regarding polymerase chain reaction results, mecA sequences were detected in 3 (18.7%) strains, whilst the tst gene encoding TSST-1 was not detected in any of clinical strains. Conclusion: It would appear that the S. aureus may be an additional negative factor worsening sperm quality and affecting male fertility. Therefore, it demands that all the patients attending in infertility treatment facilities be investigated thoroughly.